Land Modifications and Impacts on Coastal Areas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint includes papers published in the Special Issue entitled “Land Modifications and Impacts on Coastal Areas”, with the aim of collecting multidisciplinary studies concerning the evaluation of natural and anthropic drivers inducing coastal morphodynamic modifications as well as coastal environmental changes. The volume presents studies carried out by means of in situ surveys as well as analysing remote sensing data. In order to provide the reader with a wide overview on different coastal settings and methodological approaches, case studies from Bulgaria, Cameroon, Ecuador, Ghana, Italy, Mexico, North Carolina (USA), and Spain are included in this Special Issue. It is hoped that the findings will be of interest for a wide range of investigations related to coastal analysis and management, especially for researchers and academics who could utilise exploit the provided approaches and methodologies.